E-003 First Case of Flow Diverting Stent Placement in a Pediatric Patient through Radial Artery Approach. (22nd July 2019) - Bach, I; Patel, P; Majmundar, N; Khandelwal, P
Abstract : Introduction: While trans-radial access (TRA) has been previously described for coronary angiography in the pediatric population, TRA has not been well described in pediatric Neuro-intervention cases. Case: We present a case of flow diversion stent placement via the TRA in a 15-year-old female. The patient was found to have a traumatic right internal carotid artery dissection without any obvious pseudoaneurysm demonstrated on CTA and diagnostic angiography. She was started on anticoagulation. Three month follow-up MRA, demonstrated a new pseudoaneurysm measuring 8 mm x 6 mm with a neck of 4 mm. After discussion, we believed flow-diverting stent was optimal treatment in this patient. Her radial artery diameter was 2.1 mm. Ultrasound guided micropuncture of the radial artery was performed using single wall technique followed by placement of a 6-French sheath the right radial artery. 6F Envoy guide catheter was placed in the R ICA. The flow diverting stent was successfully placed without any adverse outcomes. Conclusion: Here we present feasibility of Pediatric flow diverting stent placement thought radial approach. Many Neurointerventionalists prefer transfemoral access due to familiarity as well as size of the vessel which allows for the use of larger systems. Furthermore, the TRA is often complicated by vasospasm as well as difficulty in catheterizing the contralateral ICA and VA. While there are minimal complications, the TRA carries benefits of increased comfort, faster recovery following intervention, and a significant decrease in morbidity and mortality from femoral access. As experience grows and the technique becomes more refined, we believe that TRA will become more ubiquitous for cerebrovascular intervention in the pediatric as well as adult populations. Disclosures: I. Bach: None. P. Patel: None. N. Majmundar: None. P. Khandelwal: None.